Metaheuristics Method for Classification and Prediction of Student Performance Using Machine Learning Predictors. (31st July 2022) - Kamal, Mustafa; Chakrabarti, Sudakshina; Ramirez-Asis, Edwin; Asís-López, Maximiliano; Allauca-Castillo, Wendy; Kumar, Tribhuwan; Sanchez, Domenic T.; Rahmani, Abdul Wahab
Abstract : Over the last few decades, there has been a gradual deterioration in higher education in all three areas: the academic setting (both staff and students), as well as research and development output (including graduates). All colleges and universities are essentially focused on improving management decision-making and educating pupils. High-quality higher education can be obtained through a variety of methods. One method is to accurately forecast pupils' achievement in their chosen educational context. There are numerous prediction models from which to pick. While it is unclear whether there are any markers that can predict whether a kid will be an academic genius, a dropout, or an average performer, the researcher reports student achievement. This article presents a metaheuristics and machine learning-based method for the classification and prediction of student performance. Firstly, features are selected using a relief algorithm. Machine learning classifiers such as BPNN, RF, and NB are used to classify student academic performance data. BPNN is having better accuracy for classification and prediction of student academic performance.